The Nature of the Safe Deposit Box Contract: With an Approach to Iranian National Bank (Bank-e-Melli) Robbery - Moosa Akefi Ghaziani; Gholamnabi Feyzi Chekab; Vahid Akefi Ghaziani (پژوهشهای حقوقی)
For many years, Western and Eastern Judges and Lawyers have differed on the nature of the bank's Safe deposit box contracts. They assess the nature of the present contract on the basis of legal relations and, according to it, discover the will of the parties. Some have accepted the relationship between the client and the bank as bailor and bailee, some offered lessor and the lessee, and others advised the indefinite contract as the nature of this contract. Of course, in the case of an indefinite contract, some authors consider this contract to be a mixture of bailment and lease. In this paper, in a descriptive-analytical, inferential, and practical aspect regarding Bank-e-Melli’s contract with the clients, we have firstly answered the main question of which relationship prevails between the National Bank and the clients and secondly is the indefinite contract a mixture of the two main effects of bailment and lease or not? Generally speaking, the answer to the first question is that the contract governing the relationship of the two is indefinite and the answer to the second question is negative.